Coaching systemically : five ways of thinking about systems - Lawrence, Paul, 1963- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book provides an accessible and clear description of key theories of systemic coaching and how they can be applied to coaching practice. Structured around five different ways of thinking about systems, the book provides coaches with a high-level overview of different systems theories and how those theories may be applied in practice. Readers are invited to consider each of the five different ways of thinking through the lens of philosophy, purpose and practice: Which theories most resonate for you? How do these systemic perspectives shape your purpose for coaching, and how do they show up in the way that you coach? With examples and case material throughout, Coaching Systemically aligns coaching with the realities and challenges of organisations operating in an ever more complex world. Readers will walk away from the book with a clearer understanding of what it means to coach 'systemically' and new ideas as to how they can translate insights into practice. Coaching Systemically will be key reading for coaches in practice and in training, consultants and anyone interesting in systemic approaches"--
OCLC-licensed vendor bibliographic record.
Keywords: Executive coaching; Employees -- Coaching of; Personal coaching; PSYCHOLOGY / Industrial & Organizational Psychology; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / General